Analisis Kepuasan kerja guru berdasarkan faktor Lingkungan kerja, Kepemimpinan Kepala Sekolah dan Motivasi Guru (Studi pada Guru SD Negeri di Kabupaten Bireuen) - Fadhlan, Fadhlan; Iskandar, Raihan (Aceh Cooperative Care, 2022)
ABSTRACT: Research on teacher job satisfaction is part of the evaluation and input for teacher development. Many things affect it, in this case it is limited by analyzing the factors of the work environment, principal's leadership and teacher motivation. By taking the object of research the teacher of State Elementary School (SD) in Bireuen Regency. The analysis uses the path model, to determine the direct and indirect effects of each factor due to a causal relationship between factors. The results of the analysis show; (1) there is a significant direct and indirect effect of the work environment on teacher job satisfaction by 23.95%. (2) there is a direct and indirect influence of the principal's leadership on teacher job satisfaction by 30.43%, (3) motivational factors have a significant direct or indirect effect on teacher job satisfaction that is equal to 25.5% (4) Simultaneously work environment, principal leadership and work motivation affect teacher job satisfaction by 33.2%. And (5) the level of job satisfaction of State Elementary School (SD) teachers in Bireuen Regency has not been maximized, only reaching 74.65%